Etnomatematika Motif Tenun Karaja Lamboya: Analisis Struktur Geometri dan Makna Filosofis dalam Tradisi Sumba Barat - Mitra Permata Ayu; Lidia Lali Momo (Universitas Muhammadiyah Surabaya, 2026)
Ethnomathematics is present and innovated through the culture of certain communities, one of which is reflected in the Karaja weaving. The Karaja weaving motif is one of the local cultural heritages that has a simple geometric pattern but is full of philosophical meaning. The purpose of the study is to integrate: 1) the geometric structure found in the Lamboya Karaja weaving motif; 2) the philosophical meaning contained in each Lamboya Karaja weaving motif according to the views of the customary rato. This study uses a qualitative method with a holistic ethnographic approach. Researchers are directly involved in the data collection process and act as the main instrument through the collection of participant observations, in-depth interviews and documentation. The analysis technique is simultaneous and through 4 stages, namely (1) Domain; (2) taxonomy; (3) componential and (4) cultural themes. The results of the study obtained 1) Karaja weaving has eight geometric structures, namely rhombus, isosceles triangle, rectangle, parallelogram, parallel lines, translation, reflection and folding symmetry; 2) The Karaja ikat woven motif has nine main motifs with philosophical meanings: reba, katari bula, lawata gege, ketupat, pu nabu, uma, kabedo nipe, mamoli, and nyale. This research contributes to providing a theoretical basis for ethnomathematics based on local wisdom that can be implemented as contextual geometry learning materials and media to improve students' mathematical and cultural literacy.